INNOVATIVE METHODS OF TEACHING ENGLISH - ADVANTAGES AND POSSIBLE DIFFICULTIES - Dilnoza Oblokulova (The Conference Hub, 2025)
Foreign language fluency is highly valued in today's world, making it not only a crucial component of education but also a requirement for social adaption and successful career advancement in an increasingly globalized culture. This article's goal is to examine the most successful cutting-edge approaches of teaching English, point out their benefits and potential implementation challenges, and make suggestions for how the Uzbek educational system may adopt them.